Zelotes erebeus (Thorell, 1871) (Araneae: Gnaphosidae) in Poland and its distribution in Europe - Rozwałka, Robert; Rutkowski, Tomasz; Sienkiewicz, Paweł; Zawal, Andrzej (Entomologica Fennica, 2016)
Zelotes erebeus (Thorell, 1871) is a thermophilic species occurring in southern, western and central Europe. It was excluded from the checklist of Polish spiders because of synonymization issues. This paper corrects the published data and lists new localities in western and central Poland. The sites of Z. erebeus discovered near Swinoujscie, Czarnków and Torun, move northwards the northern range limit of this thermophilous species in Europe. Data on the distribution of this species in eastern Europe and the Caucasus are also corrected - these records relate to the closely related species Z. khostensis Kovblyuk & Ponomarev, 2008. Figures of female and male genitalia of Z. erebeus are presented.